Numerical Investigation on the Effect of Guide Vane Configurations and Inclination Angles on the Performance of Gravitational Vortex Water Turbines - Erna Septyaningrum; Ridho Hantoro; Kintania Sisca Rivana (Jurnal IPTEK, 2025)
Gravitational Vortex Water Turbines (GVWTs) represent an emerging solution for low-head micro-hydropower applications, offering environmentally friendly energy conversion with minimal ecological disruption. This study investigates the effects of guide vane (GV) configurations and inclination angles on the hydrodynamic performance of GVWTs using Computational Fluid Dynamics (CFD) simulations. Various guide vane configurations—6, 7, and 9 vanes—were analyzed under inclination angles of 15°, 30°, and 45°, and evaluated across rotational speeds of 200, 300, and 400 RPM. The results reveal that both the number of vanes and their inclination angles significantly influence torque generation, tangential velocity distribution, recirculation patterns, and overall turbine efficiency. Higher inclination angles increase tangential velocity, enhancing torque, while excessive vane quantity induces flow blockage, increasing hydraulic losses. The optimal performance was achieved with 6 vanes GV at a 45° inclination, generating a maximum torque of 0.1305 Nm and achieving an efficiency of 60% at 400 RPM. Flow visualization confirmed improved streamline alignment and reduced recirculation for this configuration. These findings provide valuable insights into guide vane optimization for enhancing GVWT performance, supporting the development of efficient micro-hydropower systems for sustainable decentralized energy generation.